2017
DOI: 10.1002/ijgo.12315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic inflection points among long‐term survivors of advanced epithelial ovarian cancer

Abstract: Survival for 8 years might represent a prognostic inflection point for long-term survival in advanced EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Even though there is a high initial response rate to first-line platinum or taxane chemotherapy, most patients with ovarian cancer suffer from recurrences. Commonly diagnosed at an advanced stage, aggressively progressive characteristics have been identified as a major obstacle to the long-term remission of ovarian cancer, and an effective strategy is required for overcoming cancer progression, including migration and invasion [27]. In this study, we focused on E2F8 as a potential target for the inhibition of ovarian cancer progression.…”
Section: Disussionmentioning
confidence: 99%
“…Even though there is a high initial response rate to first-line platinum or taxane chemotherapy, most patients with ovarian cancer suffer from recurrences. Commonly diagnosed at an advanced stage, aggressively progressive characteristics have been identified as a major obstacle to the long-term remission of ovarian cancer, and an effective strategy is required for overcoming cancer progression, including migration and invasion [27]. In this study, we focused on E2F8 as a potential target for the inhibition of ovarian cancer progression.…”
Section: Disussionmentioning
confidence: 99%
“…Approximately 1,900 stage III aggressive EOC patients were included into a study conducted by Winter and colleagues; they identified the independent predictors of poor prognosis in stage III EOC patients, including mucinous or clear-cell histology, increasing age, impaired performance status, and gross residual disease (RD), which have been widely recognized so far ( 7 ). Additionally, recent extensive studies have focused on identifying the clinicopathological factors that LTS possessed in advanced EOC ( 4 , 8 - 11 ). While there is a deficiency of information in the literature on the early recognition of short-term survivor (STS) of advanced EOC to date, some prognostic factors of ovarian cancer were well-known, but we have hardly found any research on tumor size and omental metastasis that affected the overall survival (OS) in advanced EOC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic role of histological subtypes on the survival outcome among long-term survivors of advanced EOC has been explored by limited studies. A previous study by Son et al [ 27 ] reported that 91% of deaths occurred within 8 years, and that survival for 8 years may represent the prognostic inflection point for long-term survival in advanced EOC. However, only 11 patients survived for >8 years in the Son et al’s [ 27 ] study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Son et al [ 27 ] reported that 91% of deaths occurred within 8 years, and that survival for 8 years may represent the prognostic inflection point for long-term survival in advanced EOC. However, only 11 patients survived for >8 years in the Son et al’s [ 27 ] study. In our study, approximately 80% of ovarian cancer–related deaths occurred in <5 years.…”
Section: Discussionmentioning
confidence: 99%